Pour sortir de la confusion, apprendre par l'histoire selon le jeune Guizot, d'après « Les voyages d'Adolphe » (Les Annales de l'éducation, 1811-1812) - Anne Ruolt (Université de Provence, 2017)
This contribution is part of the history of educational thought. It concerns the educational ideas of the young Guizot before his entry into politics. From the Annales de l'éducation (1811-1813), and more particularly Les voyages d'Adolphe (1811-1812), this article explores the function of Guizot's teaching of history, as a way of contributing to the training of youth, and thus to show society a way out of intellectual and moral confusion to contribute to the progress of civilization. The article shows that, for Guizot, this involves training youth in the "intelligence of historic facts", to unravel the truth from the false from fundamental principles or anchors and from a compass that makes sense by the way of a not sophistic reason.